SEISMIC PERFORMANCE OF A MOMENT RESISTING FRAME WITH ENERGY DISSIPATIVE SEMI RIGID CONNECTIONS - Dogramaci Aksoylar, Nihan; Ozturk, A. Zafer (YILDIZ TECHNICAL UNIV, 2010)
A low rise long span frame with energy dissipation zones in semi rigid connections, instead of beam ends, is designed in high seismic areas and its seismic performance is evaluated analytically. To achieve this, three story three bay symmetric frames are designed by using rigid and %60 capacity connections. Seismic performances of these frames are evaluated and compared with eigenvalue analyses, nonlinear pushover analyses and nonlinear time history analyses. 25 real strong ground motion records are scaled to three earthquake levels and 150 time history analyses are conducted for two sample frames. As a result of analyses periods, capacity curves, local and global limit states, plastic hinge occurrence locations and sequence, maximum shear forces - maximum displacements, story drifts, beam and column stresses and chord rotations, are determined. Finally results are compared with acceptance criteria of FEMA 356.
Keywords: Moment resisting frame; semi rigid connection; seismic performance; nonlinear pushover analysis; nonlinear time history analysis; Engineering